Assessing the Role of Cultural Diversity in Shaping Organizational Performance and Customer Satisfaction in the Hospitality Sector: A Quantitative Approach - Gurung, Amrit Kumar; K.C., Amit; Sharma, Ashok; Timalsina, Prajit Kumar (NPRC Journal of Multidisciplinary Research, 2024)
The hospitality sector staff is noted for being multicultural, as is its customer. Understanding the complexities of cultural diversity is crucial for efficient hospitality management as businesses work to establish inclusive and culturally sensitive settings. In the context of the hospitality sector, this paper aims to investigate the effects of cultural diversity on organizational performance and consumer satisfaction. A representative sample of workers in the hotel sector is given a standardized questionnaire. The survey measures demographic traits, attitudes toward cultural diversity, perceptions of inclusion, and the effects of diversity on business performance and customer happiness. Since the data are quantifiable, statistical analysis may be used to find trends, correlations, and the overall impact of cultural diversity on many aspects of hospitality management. The study's findings add to the body of knowledge on cultural diversity in the hospitality sector by providing insights into the tactics and methods that improve industry efficiency and customer happiness. The study emphasizes the need of developing a welcoming and inclusive company culture that values diversity, encourages cultural awareness, and capitalizes on the distinctive skills and viewpoints of employees from all origins.